Ho, Ping-Ti y Tang Tsou (Ed.), China in crisis: China’s Heritage and the Communist Political System. Vol. 1, libros 1 y 2. University of Chicago Press, 1968. - T. C., J. (Estudios de Asia y África, 1970)
-